Composition of Energy Drink Samples in Bangladesh (Dhaka University Journal of Science, 2022)
The commercial energy drink samples of 10 different brands were analyzed to study the level of alcohol (if any), sodium benzoate,caffeine, vitamin B, and carbohydrates content. Samples were degassed by ultrasonicator, and CO2 was found to be in a range of 1.27± 0.05 to 4.10 ± 0.10 mL per 100 mL sample. The amount of caffeine, sodium benzoate, glucose, and vitamin B were studied by aUV-Visible spectrophotometer. The wavelength of absorption maxima was 224, 272, 489, 445, and 292 nm, respectively, for sodiumbenzoate, caffeine, glucose, vitamin B2, and vitamin B6. The correlation coefficients of the calibration curves were found to be0.998, 0.992, 0.998, 0.997, and 0.989 for caffeine, glucose, sodium benzoate, vitamin B2 and vitamin B6, respectively. The alcoholcontent was studied by gas chromatography equipped with a flame ionization detector. Ethanol was not found to be present in anysample. The caffeine and sodium benzoate content in different samples was found in the range of 147.84 ± 0.53 to 846.78 ± 2.64 and52.92 ± 6.23 to 1575.37 ± 4.99 μg/mL, respectively. The sugar content in different samples was found to be 16.16 ± 4.25 to 338.33± 0.75 mg/mL. Vitamin B2 was found to be 13.21± 0.08 and 1.04 ± 0.002 μg/mL, respectively in Bacchus and Wild Brew samplesand Vitamin B6 was found to be 261.17 ± 8.38 and 115.88 ± 0.31 μg/mL in Red Bull and Bacchus samples, respectively. The pH ofthe samples was found to be in the range of 2.79 ± 0.04 to 4.88 ± 0.04.Dhaka Univ. J. Sci. 70(1): 42-48, 2022 (January)